Pre-Hypertension among Young Adults (20–30 Years) in Coastal Villages of Udupi District in Southern India: An Alarming Scenario - Kini, Sanjay (PLoS One, 2016)
INTRODUCTION: According to Joint National Committee-7 (JNC-7) guidelines, a systolic blood pressure (SBP) of 120 to 139 mm Hg and/or diastolic blood pressure (DBP) of 80 to 89 mm Hg is considered as pre-hypertension. Existing evidence suggest that the cardiovascular morbidities are increasing among pre-hypertensive individuals compared to normal. OBJECTIVE: To assess the magnitude and factors associated with pre-hypertension among young adults (20–30 years) in coastal villages of Udupi Taluk (an area of land with a city or town that serves as its administrative centre and usually a number of villages), Udupi District, Karnataka state, India. DESIGN: Community based cross sectional study SETTING: 6 (out of total 14) coastal villages of Udupi Taluk, Karnataka state, India. SAMPLE: 1,152 young adults (age group: 20–30 years) selected by stratified random sampling in 6 coastal villages of Udupi Taluk, Karnataka state, India METHOD: A semi structured pre-tested questionnaire was used to elicit the details on socio-demographic variables, dietary habits, tobacco use, alcohol consumption, physical activity, family history of hypertension and stress levels. Anthropometric measurements and blood pressure were recorded according to standard protocols. Serum cholesterol was measured in a sub sample of the study population. Multivariate logistic regression was applied to identify the independent correlates of pre-hypertension among young adults (20–30 years). MAIN OUTCOME MEASURES: Prevalence, Odds ratio (OR) and adjusted (adj) OR for pre-hypertension among young adults (20–30 years). RESULTS: The prevalence of pre-hypertension in the study population was 45.2% (95%CI: 42.4–48). Multivariate logistic regression analysis revealed that age group of 25–30 years (adj OR: 4.25, 95% CI: 2.99–6.05), white collared (adj OR: 2.29, 95% CI: 1.08–4.85) and skilled occupation (adj OR: 3.24, 95% CI: 1.64–6.42), students (adj OR: 2.46, 95% CI: 1.22–4.95), using refined cooking oil (adj OR: 0.53, 95% CI: 0.29–0.95), extra salt in meals (adj OR: 2.46, 95% CI: 1.52–3.99), salty food items (adj OR: 6.99, 95% CI: 3.63–13.48), pre-obese (adj OR: 1.66, 95% CI: 1.03–2.67) and obese (adj OR: 9.16, 95% CI: 2.54, 36.4) were the significant correlates of pre-hypertension. CONCLUSION: In the study population, prevalence of pre-hypertension among young adults (20–30 years) was high (45.2%). Biological (age 25–30 years, pre-obesity and obesity) and behavioral (sedentary occupation, intake of extra salt in meals/salty food and not using refined cooking oil) factors were associated with pre-hypertension. Study emphasizes the need of community based screening of pre-hypertension under National Rural Health Mission. It also provides apt information for the evidence based designing of interventions for lifestyle modifications among high risk young adults in the study area.